2022
DOI: 10.1126/scitranslmed.abn2263
|View full text |Cite
|
Sign up to set email alerts
|

Nonlesional lupus skin contributes to inflammatory education of myeloid cells and primes for cutaneous inflammation

Abstract: Cutaneous lupus erythematosus (CLE) is a disfiguring and poorly understood condition frequently associated with systemic lupus. Previous studies suggest that nonlesional keratinocytes play a role in disease predisposition, but this has not been investigated in a comprehensive manner or in the context of other cell populations. To investigate CLE immunopathogenesis, normal-appearing skin, lesional skin, and circulating immune cells from lupus patients were analyzed via integrated single-cell RNA sequencing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 44 publications
6
55
0
Order By: Relevance
“…Given the known role of heterogeneous fibroblast subsets in both activating and suppressing the local immune response, understanding whether and how upper-dermal fibroblasts are functionally contributing to or restraining disease may provide insights into mechanisms underlying PsO and related skin inflammatory conditions (53). Examination of distal uninvolved skin similarly revealed high interferon signatures in patients with cutaneous lupus (54). Whether other organs or tissues beyond the skin are also affected by inflammatory skin disease while maintaining their normal function, or whether signatures of skin inflammation are uniquely observed in distal skin, remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Given the known role of heterogeneous fibroblast subsets in both activating and suppressing the local immune response, understanding whether and how upper-dermal fibroblasts are functionally contributing to or restraining disease may provide insights into mechanisms underlying PsO and related skin inflammatory conditions (53). Examination of distal uninvolved skin similarly revealed high interferon signatures in patients with cutaneous lupus (54). Whether other organs or tissues beyond the skin are also affected by inflammatory skin disease while maintaining their normal function, or whether signatures of skin inflammation are uniquely observed in distal skin, remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…2B). Please note that we did not use uninvolved psoriatic skin as control, since it had recently been shown in lupus erythematosus that macroscopically uninvolved skin may be in a preactivated inflammatory stage [20]. All other cell types did not show different percentages of positive cells (data not shown).…”
Section: Mapping Of Cytokines On Cellular Subtypesmentioning
confidence: 94%
“…PDC infiltrates are observed in a great proportion of skin biopsies and can form clusters in CLE skin lesions [ 38 , 40 ]; however, not all skin lesions harbor a pDC infiltrate [ 41 ]. Recently, single-cell ribonucleic acid (RNA) and spatial RNA sequencing has shown that even healthy-appearing skin of CLE patients contains a type I IFN-rich environment and that CD16+ DCs undergo IFN priming in the skin, leading to proinflammatory subtypes [ 42 ]. Because of their central role in CLE pathophysiology, pDCs are an attractive therapeutic target.…”
Section: Pathogenesismentioning
confidence: 99%